Contribution of Ibn Khaldun's Thought to the Modern Economic Model: A Historical-Sociological Analysis - Humaerah Humaerah; Faiz Afza Ihsan; Muaz Tanjung (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
The urgency to revisit the intellectual foundations of modern economics is growing amidst institutional instability, economic inequality, and the challenges of sustainable development, making Ibn Khaldun's thought relevant again as a comprehensive conceptual alternative. This article aims to analyze the contribution of Ibn Khaldun's economic thought to the modern economic model through a historical-sociological approach, by examining how the 14th-century social, political, and cultural context shaped his theoretical framework and assessing its relevance to contemporary economic theory and practice. This research uses a qualitative method with a literature study design, utilizing primary data from Al-Muqaddimah and secondary data from various academic studies, which are analyzed through data reduction, thematic categorization, and comparative interpretation techniques. The results show that Ibn Khaldun's concepts-such as 'asabiyyah, the work-based theory of value, market mechanisms, the role of the state, distributive justice, and the cycle of civilization-have strong correspondences with modern institutional economics, behavioral economics, and fiscal theory, including the Laffer curve principle and the institution-based growth model. These findings enrich the study of the history of economic thought and offer a more integrative analytical framework for understanding the relationship between social stability, institutional quality, and economic performance. The study's conclusions confirm that Ibn Khaldun's thoughts possess not only historical value but also practical relevance for developing equitable and sustainable economic policies. Further studies are recommended to empirically test the key variables in Ibn Khaldun's model using quantitative or mixed-method approaches to expand the validity and applicability of the findings.